Depoliticisation via europeanisation? - Pandžić, Josip (Teorija in praksa, 2025)
The Croatian security intelligence system’s historical development was shaped significantly by politicisation, which has laid the foundations for many of the intelligence community’s current issues. In order to corroborate this assertion, different political impacts as well as politicised security intelligence practices are presented in the article using a historical-institutional approach, where both determined the periods before and after the 1990s, the key demarcation point being the attainment of independence in 1991. Over a decade after joining the European Union (EU), it is argued that the multidimensional Europeanisation process is one of the central factors in the depoliticisation of national security intelligence in Croatia.
Keywords: europeanisation; evropeizacija; intelligence; obveščevalne dejavnosti; politicisation; politizacija, Hrvaška, varnost, obveščevalne dejavnosti, evropeizacija; safety; varnost